Real-World Multiple Comparison of Transcatheter Aortic Valves: Insights From the Multicenter OBSERVANT II Study. (9th December 2022) - Costa, Giuliano; Barbanti, Marco; Rosato, Stefano; Seccareccia, Fulvia; Tarantini, Giuseppe; Fineschi, Massimo; Salizzoni, Stefano; Valvo, Roberto; Tamburino, Corrado; Biancari, Fausto; Baglio, Giovanni; Santoro, Gennaro; et al.
Abstract : Background: Head-to-head comparisons of devices for transcatheter aortic valve implantation (TAVI) are mostly limited to 2-arm studies so far. The aim of this study was to compare simultaneously outcomes of the most used, second- and third-generation transcatheter aortic valves in a real-world population. Methods: A total of 2728 patients undergoing TAVI with different second- and third-generation devices, and enrolled in the multicenter, prospective OBSERVANT II study (Observational Study of Effectiveness of TAVI With New Generation Devices for Severe Aortic Stenosis Treatment) from December 2016 to September 2018 were compared according to the transcatheter aortic valve received. Outcomes were adjudicated through a linkage with administrative databases, and adjusted using inverse propensity of treatment weighting. The primary end point was the composite of all-cause death, stroke and rehospitalization for heart failure at 1-year. Rates were reported consecutively for Evolut R, Evolut PRO, SAPIEN 3, ACURATE neo, and Portico groups. Results: The primary end point did not differ among groups (23.9% versus 24.7% versus 21.5% versus 23.7% versus 27.4%, respectively, P =0.56). Permanent pacemaker implantation was significantly lower for patients receiving SAPIEN 3 (19.9% versus 19.3% versus 12.5% versus 14.7% versus 22.1%, respectively, P <0.01) at 1 year. The SAPIEN 3 had lower rates of paravalvular regurgitation (moderate-to-severe grade 10.1% versus 5.0% versus 2.1% versus 13.1% versus 10.8%, respectively, P <0.01) but higher transprosthetic gradients (median mean gradients 7.0 versus 6.0 versus 10.0 versus 7.0 versus 8.0 mm Hg, respectively, P <0.01) after TAVI. Conclusions: Data from real-world practice showed low and comparable rates of complications after TAVI considering all the available devices. Patients receiving SAPIEN 3 valve had lower rates of paravalvular regurgitation and permanent pacemaker implantation, but higher transprosthetic gradients.